Study on the impact of learning engagement on the subjective wellbeing of empty nesters in rural China - Zeng, Ruirang; Shi, Huiqin; Wu, Huiqi; Sun, Lixin (Frontiers in Psychology, 2024)
With the rapid development of China's socio-economic landscape and shifts in population structure, rural empty nesters have increasingly become a focal point of social concern. Compared to their urban counterparts, rural empty nesters face more life challenges and psychological stress, making their subjective wellbeing a significant issue. This study explores the impact of learning engagement on the subjective wellbeing of rural empty nesters in China, aiming to provide theoretical support and policy recommendations to enhance their wellbeing. Using a random sampling method, the study focused on elderly learners aged 50 and above from counties within Z Province, N City, where elderly learning is relatively concentrated. Data were processed using SPSS 27.0 software. The findings indicate that there is a significant difference in subjective wellbeing between rural empty nesters and rural non-empty nesters, with rural empty nesters exhibiting lower subjective wellbeing and more passive involvement in learning activities. Learning engagement has a significant effect on improving the subjective wellbeing of rural empty nesters, with a notable positive correlation between learning engagement dimensions and subjective wellbeing. Compared to rural non-empty nesters, learning engagement has a more pronounced positive effect on the subjective wellbeing of rural empty nesters.